Requirements for activating the digital economy in the education sector in Oman to face challenges and crises – the case of Covid-19 pandemic - Alhinai, Salman Sloum Khamis; Ismail, Omer Hashim; AlAbri, Khalaf Marhoun; AlMusawi, Ali Sharaf Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to establish a digital economy base in the education sector, instill a digital economic culture in institutions and individuals, build an effective educational digital economy, activate its role in facing the education sector's challenges and know the reality and requirements necessary to activate. The qualitative approach was used, and many local and global subject-relevant studies and documents were analysed. Several results were reached, the most important: education in the Sultanate of Oman faces several challenges, including (reliance on the government as a primary financing source, lack of income source diversification, high costs of technical projects, Fourth Industrial Revolution requirements, and legislative regulations that are not supportive of technology investment. The Ministry of Education`s efforts contributed to the digital transformation during the COVID--19 pandemic by facing the crisis and reducing educational and economic losses. Currently, there is no planned investment for the technical projects applied in the ministry economically. The digital economy contributes to diversifying income sources and reducing the burden on the budget. The digital economy activates education through technology production, application, and investment. Among the requirements for activating the digital economy at the institutional level (digital transformation, technological investment supporting plans, instilling a digital economy culture, processes re-engineering, enabling policies and legislation system, updating structural systems, establishing technological infrastructure, strategic decision). At the educational process level (modifying the study plan, including technology study materials, providing laboratories and a stimulating environment, activities, and events to support innovation in schools, motivating and supporting innovators by the government and private sectors, and encouraging technological investment).
Keywords: digital economy; technological innovation; digital transformation; education sector; Information and Communication Technology